TATA KELOLA TEKNOLOGI INFORMASI RUMAH SAKIT KUSTA DOKTER RIVAI ABDULLAH PALEMBANG - Rizal, Syahril ; Rasmila, Rasmila (Universitas Bina Darma, 2015)
Abstract: Evaluation of information technology governance, especially computers and IT Governance in government hospitals is in need, so that the development of ICT in the hospital could be developed following the modernization era is rapidly increasing. ICT in the hospital is in need to serve the community by working operasional standards to facilitate the work and increase IT investment destination hospital itself. Hospital of Dr Rival Abdullah Palembang currently have implemented computer information technology. Based on the evaluation process that has been conducted using the COBIT 5.0 it can be stated that the results of recapitulation level capability scale model of evaluation research IT governance at Leprosy Hospital Dr. Rivai Abdullah Palembang is the scale 2 (managed process) with a value of 1.83, which it means that the Leprosy Hospital Dr. Rivai Abdullah Palembang already planning and implementation of Information Technology governance computers today by using predefined planning process. Keywords: Evaluation, Governance, COBIT 5, Capability Model